PENGARUH PRODUK BANK SYARIAH TERHADAP MINAT MENABUNG DENGAN PERSEPSI MASYARAKAT SEBAGAI VARIABEL MODERATING DI PATI - Rusdianto, Hutomo; Ibrahim, Chanafi (EQUILIBRIUM, 2016)
This study aimed to know the products of Sharia Banks, especially in Kota   Pati district toward the interest of saving money by using the public perception as moderating. This research used descriptive quantitative method with populations Islamic Banking (BRI Syariah, BNI Syariah, Mandiri Syariah, Bank Jateng Syariah, Bank Muamalat) in Kota Pati district. The samples were the people who made transactions in Syaria Conventional  Banks  totaling  100  respondents  taken  using quota  sampling  technique.  Methods  of  data  analysis  used MRA (Moderating Regresion Analysis) test. The results of this study showed that the products of existing Islamic banks in microfinance particularly in Kota  Pati distrcit has impacts on people. It proves that the products (savings) of microfinance have benefits for customers. While the public perception can be moderating variables because the public banks can give education to the society that their products are free from usury.